Layout optimization of injection process by considering integrated resilience engineering: a fuzzy-DEA approach. (2nd January 2021) - Navazi, Fatemeh; Tavakkoli-Moghaddam, Reza; Memari, Pedram
ABSTRACT: According to the impact of the layout design on the performance of high volumes production line, a single-row facility layout problem is considered in a process diagnosed as a bottleneck. In this regard, a discrete-event-simulation method is employed for modeling all possible layouts of an injection process. The results of the fuzzy simulation are imported to the output-oriented fuzzy data envelopment analysis (F-DEA) to rank different layouts as decision-making units. Then, the optimum layout is selected by considering the average waiting time and utility of resource as traditional key performance indicators, in addition to fault-tolerant, flexibility, and teamwork as resilience engineering (RE) factors. Also, the results are validated and verified by using some statistical tests. The sensitivity analysis is performed to find the most influential factor and weight of each factor. This is the first study to model the RE factors in the injection molding process by using the F-DEA method. Herein, a unique fuzzy mathematical-simulation model is tailored. Finally, the solution quality is pointed by a real case study in a refrigerator injection process of a home appliances company.